Joshua Dibundu, Lotin Same, and the Native Baptist Church: Resistance and Nationalism in Cameroon’s History of Religion - Roland Ndille (Modern Africa)
This article sets out to present Joshua Dibundu and Lotin Same, two clergymen and contemporaries of John Chilembwe of Nyasaland and Simon Kibangu of the Congo, who stood out against European missionary pressure and colonial administrative oppression in an effort to establish and sustain the first African Independent Church (AIC) in Cameroon: the Native Baptist Church (NBC). I argue in this article that unlike the Cameroon kings and chiefs who resisted European occupation of the territory, and nationalists who fought for independence, the leaders of the Native Baptist Church represent another type of early nationalist and change-oriented agents who deserve their place in the historiography of the country. I have privileged the use of archival documents, structured interviews and some critical empirical literature to establish this account.